1999
DOI: 10.1007/s001470050252
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of conversion of complement-dependent cytotoxic T cell crossmatch test after renal transplantation

Abstract: The purpose of this study was to investigate the clinical relevance of conversion of post-transplant T cell crossmatch between kidney donor and recipient. This study comprises 892 cadaveric renal transplantations performed on 874 adult patients between August 1991 and December 1997. Recipient selection was based on a negative complement-dependent cytotoxic T cell crossmatch test with current (< or = 2 months old) serum. For this study, on day 0 and day 14 after transplantation, serum samples were collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(4 reference statements)
0
1
1
Order By: Relevance
“…Because immunologically high-risk patients were excluded from this study, it is not surprising that overall DGF (17.4%) and rejection frequencies (14.8%) were substantially lower than in our previous study (10). This may, at least in part, explain the finding that T-cell IgG FCXMs did not convert to positive except in two of these study patients during the follow-up of 1 year.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Because immunologically high-risk patients were excluded from this study, it is not surprising that overall DGF (17.4%) and rejection frequencies (14.8%) were substantially lower than in our previous study (10). This may, at least in part, explain the finding that T-cell IgG FCXMs did not convert to positive except in two of these study patients during the follow-up of 1 year.…”
Section: Discussioncontrasting
confidence: 64%
“…We have previously demonstrated that conversion of T-cell crossmatch to positive on day 14 after transplantation, especially in connection with DGF, identified a subgroup of patients at high risk of severe rejection and poor graft survival (10).…”
Section: Discussionmentioning
confidence: 99%